Earthquake Damage Detection in Built Environment: An Object-Oriented Approach Using Radar Imagery - Babak Mansouri (Iranica Journal of Energy and Environment, 2013)
The feasibility to develop a rapid urban seismic damage detection procedure utilizing satellite radarimagery is investigated. In direct observation of city-wide building loss, remote sensing damage detectiontechniques have shown merits in rapid damage detection in urban areas. Remote sensing technology has thecapability of extracting buildings in urban scenes. Comparing “before” and “after” images and benefiting fromimage processing techniques, it is possible to detect the extent of high hit zones. In detecting post-earthquakedamages to buildings and in order to reduce detection errors and for minimizing the false alarms, it seemslogical to apply the change detection algorithms only to the patches that correspond exactly to buildingfootprints. For this purpose, urban database revealing the 3D reconstruction of the city is developed usingparcels records. The parcels are extracted from aerial photos (stereography processing) then complemented andupdated using VHR (very high resolution) optical satellite image (i.e. Quickbird imagery). The change detectionalgorithm and the calibration modeling are applied to “before” and “after” EnviSat SAR images considering onlythe building layer. The methodology is applied to the city of Bam and the associated building damages of its2003 earthquake were emphasized. Results were compared with an independent direct visual damageinterpretation using a VHR optical image.